A reassessment of public awareness and legislative framework on cybersecurity in South Africa - Olofinbiyi, Sogo Angel (ScienceRise: Juridical Science, 2022)
Cybersecurity has become a growing concern globally, following this era of unparalleled resources, power relations and technological evolution. Technological vulnerabilities have led to massive data breaches in recent years and research has highlighted potential uses of artificial intelligence to engineer more powerful cyber-attacks thus revealing new hardware weaknesses. Cyber-attacks pose a threat to critical infrastructure thereby compelling countries to intensify their national security testing for cross-border partnerships. South Africa, however, is lagging in terms of readiness and capacity building against various forms of cyber-attack. Currently, the country has the world’s third-highest number of cybercrime victims. By the same token, there is evidence that the South African Banking Risk Information Centre (SABRIC) loses over R2.2bn annually to cyber-attacks. In October 2019, two seemingly separate syndicates of hackers threatened to close the finance and local government sectors at a time when South Africa was struggling to recover from its previous economic recession. Taking insights from the existing literature, the study demonstrates that the level of awareness of cybersecurity among the South African populace is very poor, while the legislations put in place have done little to alleviate the trends and shield the general population from cyberwarfare. With growing legislation focussing on cybersecurity, the study contends that there is also the need for diverse professional and academic institutes to deliver hands-on educative services to the society through research-led activities to ensure South Africa is resilient to the growing threats. Given the borderless nature of cybercrime, South Africa should start intensifying efforts to incorporate the Joint Cybercrime Action Taskforce (J-CAT) alongside the local laws and necessitate the establishment of police-oriented learning centres, where citizens can be educated on the dangers of cybercrime and its devastated impacts on national development. With the drive towards digital economy and advanced global technologies, there is the need for further consolidation of South Africa’s cybersecurity system with a view to ensuring the safety and security of national infrastructure, society, and global economic relations from malicious online crime spree. Until these are done, the storm is not yet over